Relationship of Electrocardiographic Left Ventricular Hypertrophy to the Presence of Diastolic Dysfunction. Issue 6 (17th April 2014) - Krepp, Joseph M.; Lin, Fay; Min, James K.; Devereux, Richard B.; Okin, Peter M.
<x xml:space="preserve">Abstract</x> Background Left ventricular (LV) diastolic dysfunction (DD) is a known predictor of poor cardiovascular outcomes. Although ECG LV hypertrophy (LVH) is strongly associated with LV systolic dysfunction and heart failure, the relation of LV DD to ECG LVH is unclear. Methods ECG LVH by Cornell product (CP) criteria was examined in a cohort of 185 patients who underwent both cardiac computed tomographic angiography and transthoracic echocardiography with complete evaluation of diastolic function. The presence of DD was determined via evaluation of mitral inflow velocities, tissue Doppler imaging, deceleration time, isovolumic relaxation time, pulmonary venous systolic: diastolic ratio, and left atrial enlargement. Results Among the 185 patients (56% female, mean age 54.6 ± 15.6), 105 (57%) had DD. In univariate logistic regression analysis, patients in the upper quartile of CP (≥1595 mm·ms) had a >5‐fold greater odds of DD (odds ratio [OR] 5.1, 95% confidence interval [CI] 2.2–11.7, P < 0.001). In alternative analyses treating CP as a continuous variable, each 1 SD increase in CP (664 mm·ms) was associated with an OR of 1.9 for DD (95% CI 1.3–2.7, P < 0.001). In multivariate logistic regression analyses adjusting for univariate predictors of DD, the highest quartile of CP remained associated with a 5.9‐fold increased odds of DD (95% CI 2.3–15.4, P = 0.001), and each 1 SD of CP with a 1.7‐fold increased odds of DD (95% CI 1.2–2.5, P = 0.005). Conclusions CP LVH is a strong predictor of DD, even after adjustment for other potential risk factors and ECG variables.